DECONSTRUCTING THE AMERICAN DREAM: AMERICA THROUGH KNUT HAMSUN’S EYES - MUREȘAN, Ioana-Andreea (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Deconstructing the American Dream: America through Knut Hamsun’s Eyes. This paper examines Knut Hamsun’s perception of the American way of living as depicted in his Fra det moderne Amerikas aandsliv (The Cultural Life of Modern America, translated into English in 1969 by Barbara Gordon Morgridge), published in Copenhagen 1889, and in one of his short stories, Raedsel (Fear, translated by Sverre Arestad), which he has published fifteen years after his return from America. Hamsun’s American experience was rather different than the one of most immigrants in America, but this article demonstrates that the Norwegian writer’s insights into the life in the New World, though bitter and inclined to criticism, must be studied in order to achieve a broader perspective upon the immigrant experience in the land of opportunities. REZUMAT. Destrămând visul american: America prin ochii lui Knut Hamsun. Lucrarea de față analizează percepția lui Knut Hamsun asupra stilului de viață american așa cum a fost descrisă în volumul Fra det moderne Amerikas aandsliv (Din viața culturală a Americii moderne – tr.n.), publicat în Copenhaga în 1889, și într-una din nuvelele sale, Raedsel (Spaimă – tr.n.), pe care a publicat-o la cincisprezece ani după reîntoarcerea din America. Experiența lui Hamsun în America a fost destul de diferită de cea a majorității imigranților, dar acest articol demonstrează că observațiile scriitorului norvegian asupra vieții în Lumea Nouă, deși acide și înclinate spre critică, trebuie studiate pentru a dobândi o perspectivă mai largă asupra experienței imigranților în țara oportunităților. Cuvinte cheie: Knut Hamsun, visul american, literature imigrației, America, norvegieni în America